A Critical Review of Environmental Conservation in Zimbabwe. Issue 2 (August 2013) - Mawere, Munyaradzi
The discourse on "environmental conservation" is highly dynamic and has generated controversies of epic proportions in conservation sciences and environmental anthropology. Given the nebulous nature of conservation, coupled with the varying interpretations evoked by the deployment of the concept across different disciplines, a more robust understanding of the notion calls into question its practical manifestations and application in particular situated contexts – particularly within the conservation sciences and environmental anthropology. In Zimbabwe, conservation by the state has tended to favour and privilege Western scientific models at the expense of the "indigenous" conservation practices of local people, as informed by their indigenous epistemologies. This paper thus represents an attempt to rethink conservation in Zimbabwe, adopting the Norumedzo communal area in south-eastern Zimbabwe as its case study. The choice of Norumedzo is based on the fact that this is one area where the highly esteemed and delicious harurwa (edible stink bugs, Encosternum delegorguei) are found. As a result of these insects being valued as "actors" and the appreciation shown to both Western and indigenous epistemologies, conservation in the area has enjoyed considerable success. To this end, this paper lends support to the arguments of Walter Mignolo and Ramon Grosfoguel in their advocacy for critical border thinking in issues of knowledge regarding environmental conservation.